The Effect of Strengths-Based School Counseling Model on Career Development and Academic Well-Being of Students - Mohammad Ranjbar (Alzahra University, 2021)
This study was done to investigate the effects of the strengths-based school counseling on the career development and the academic well-being of students. The research method was semi-experimental with pretest-posttest design and two control groups. The population included all male students from high schools of Isfahan in the academic year 1394-95, which were randomly selected from schools in a district and were placed in three different groups as experimental, control 1, and control 2 groups. Principles and programs of the strengths-based school counseling were performed on the experimental group during an academic semester. The questionnaires of the career development in short form Australia Creed and Patton and academic well-being of scale, Singly, Shou, and Schmitt were used to collect the data. The results of analysis of covariance showed that the career development scores of students in the experimental group were significantly increased compared to the other two groups, but the increase was not significant in the academic well-being. So, we can conclude that the strengths-based school counseling has a significant impact on the career development of students, but the academic well-being has not been affected.